Implementation of Education on Fire Service Policy at the Cianjur District Fire Service - Harisyanto Harisyanto; Yeti Rohayati; Diani Indah; Indriyati Kamil (Global Education Journal, 2026)
Firefighting services are a strategic form of public service that plays a crucial role in protecting public safety and property from fire risks. This study aims to analyze the implementation of firefighting service policies at the Cianjur Regency Fire Department, identify the inhibiting factors affecting their implementation, and formulate strategic efforts to improve service quality. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, field observations, and document analysis involving key informants, including structural officials, operational officers, and public service staff. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings indicate that the implementation of firefighting service policies in Cianjur Regency has been carried out but has not yet reached optimal performance. Policy communication and understanding of standard operating procedures are relatively adequate; however, limitations remain in terms of human resources, facilities and infrastructure, and budgetary support. In addition, inter-agency coordination has not been fully effective, which affects the response time in handling fire incidents. The disposition of policy implementers reflects a high level of commitment and professionalism, although it is constrained by workload and limited facilities. This study concludes that improving the quality of firefighting services in Cianjur Regency requires strengthening resources, enhancing cross-sectoral coordination, optimizing facilities and infrastructure, and continuously developing the capacity of firefighting personnel.